Comparing the efficacy and renal safety of metformin and imeglimin in diabetic rats - Ngammoiran, Charang; Singh, Thongam Ramananda; Devi, Laishram Elizabeth; Devi, L. Tarinita; Meetei, Usham Dharmaraja (International Journal of Research in Medical Sciences, 2025)
Background: Diabetic kidney disease (DKD) represents a significant cause of end-stage kidney disease and is closely linked to substantially higher rates of cardiovascular morbidity and mortality. As a result, there is a need for therapies that can prevent DKD, improve patient compliance, reduce side effects, and be cost-effective. Methods: Healthy male albino rats (150-200 g) were screened, and hyperglycemia was induced in 24 rats, and after one week, hyperglycemia was confirmed. The rats were then divided into four groups (Groups 1, 2, 3, and 4) (n=6). Group 1 was designated as diabetic control group, while nephrotoxicity was induced in the remaining rats. Group 1 and Group 2 (toxic control group) were treated with vehicle. Group 3 (metformin group) was treated with metformin, and Group 4 (imeglimin group) received imeglimin, both at a dose of 180 mg/kg/day for two weeks. Results: On day 21, there was a significant reduction in serum urea and creatinine levels in Group 3 (p<0.05 and p<0.05, respectively) and Group 4 (p<0.001 and p<0.001, respectively) when compared with Group 1. Also, both Groups 3 and 4 showed a significant reduction in serum urea (p<0.001, p<0.001) and creatinine (p<0.001, p<0.001) levels when compared with Group 2. However, the glycemic control by imeglimin did not significantly differ from that of metformin on day 21. Conclusions: Imeglimin was more effective in improving renal function parameters, demonstrating greater renal safety compared to metformin.